SUPERVISI AKADEMIK KEPALA SEKOLAH DALAM MENINGKATKAN MUTU PRMBELAJARAN DI SD MUHAMMADIYAH 03 TUMPANG KABUPATEN MALANG - Zuher, Mohammad; Warisno, Andi; Setyaningsih, Rina (UNISAN JURNAL, 2024)
Academic supervision is a series of activities to help the teachers in developing their ability to manage the learning process in order to achieve the learning targets. Supervision which was conducted by SD Muhammadiyah 03 Tumpang Kabupaten Malangwas an aid that guides the teacher in planning the learning, implementing the learning process, evaluating the students’ learning outcome, and following up the supervision’s results in order to improve the quality of learning in SD Muhammadiyah 03 Tumpang Kabupaten Malang. This study aims to: 1) describe and analyze the principal academic supervision of SMP Muhammadiyah in improving the quality of learning, 2) describe the implementation strategy of principal academic supervision of SD Muhammadiyah 03 Tumpang Kabupaten Malangin improving the quality of learning, 3) describe and analyze the implication of the principal academic supervision of SD Muhammadiyah 03 Tumpang Kabupaten Malangin improving the quality of learning.This study applied descriptive qualitative approach. The source of the data were principal, vice principal of curriculum, vice principal of quality guarantor, teachers of SD Muhammadiyah 03 Tumpang Kabupaten Malang. The data collection techniques used observation, interview, and documentation. As for the validity test using triangulation techniques data and sources, while the data analysis using interactive analysis techniques. Based on the research findings, it could be concluded as follows: (1) the principal’s of SD Muhammadiyah 03 Tumpang Kabupaten Malangacademic supervision programs were prepared based on the supervision analysis results and the previous monitoring results of the learning process; the principal’s academic supervision programs were arranged at the beginning of the school year by identifying the problems, setting the goals, and determining the implementation time in advance. Those activities engaged the roles of vice principal of curriculum, vice principal of quality guarantor, and teachers that were done systematically, (2) the implementation strategy of the principal’s academic supervision included: indirect and direct supervision, classroom visit supervision, and observation of the teachers’ activity inside as well as outside the classroom, and the following-up implementation of academic supervision result in the form of personal and group coaching. (3) the implication of principal’s academic supervision were: (a) the improvement in the teachers’ ability in designing learning sets (b) the improvement in the teachers’ ability in implementing the learning process, (c) the improvement in the teachers’ ability in evaluating the students’ learning outcomes.